Review of the application of vegetation remote sensing - SHEN Guang-rong; WANG Ren-chao (浙江大学学报. 农业与生命科学版, 2001)
Vegetation remote sensing data plays an important role in monitoring dynamically earth resource from the space. In this paper, the application of vegetation remote sensing in detecting the vegetation growth state, estimating the canopy biochemical characteristics and productivity of crop from vegetation remote sensing data ware reviewed in detail. The special attention to the recent works about the integration of multiangle remote sensing and hyperspectral remote sensing data to invert accurately vegetation parameters ware given. Finally the paper discussed the way and studied fields of the further application of remote sensing information.